Outcomes of patients with cirrhosis and hepatorenal syndrome type 1 treated with liver transplantation. Issue 3 (10th February 2015) - Wong, Florence; Leung, Wesley; Al Beshir, Mohammed; Marquez, Max; Renner, Eberhard L.
Abstract : Hepatorenal syndrome type 1 (HRS1) is acute renal failure in the setting of advanced cirrhosis, and it results from hemodynamic derangements, which should be fully reversible after liver transplantation. However, the rate of hepatorenal syndrome (HRS) reversal and factors predicting renal outcomes after transplantation have not been fully elucidated. The aim of this study was to assess outcomes of HRS1 patients after liver transplantation and factors predicting HRS reversal. A chart review of all liver transplant patients with HRS1 (according to International Ascites Club criteria) at Toronto General Hospital from 2001 to 2010 was conducted. Patient demographic data, pretransplant and posttransplant laboratory data, and the presence of and time to posttransplant HRS reversal (serum creatinine < 1.5 mg/dL) were extracted from the center's transplant electronic database. Patients were followed until death or the end of the 2011 calendar year. Sixty‐two patients (mean age, 54.7 ± 1.2 years; mean Model for End‐Stage Liver Disease score, 35 ± 1) with HRS1 (serum creatinine, 3.37 ± 0.13 mg/dL) at liver transplant were enrolled. Thirty‐eight patients received midodrine, octreotide, and albumin without success and subsequently received renal dialysis. One further patient received dialysis without pharmacotherapy. After liver transplantation, HRS1 resolved in 47 of 62 patients (75.8%) at a mean time of 13 ± 2 days. Patients without HRS reversal had significantly higher pretransplant serum creatinine levels (3.81 ± 0.34 versus 3.23 ± 0.14 mg/dL, P  = 0.06), a longer duration of HRS1 {25 days [95% confidence interval (CI), 16‐42 days] versus 10 days (95% CI, 10‐18 days), P  = 0.02}, a longer duration of pretransplant dialysis [27 days (95% CI, 13‐41 days) versus 10 days (95% CI, 6‐14 days), P  = 0.01], and increased posttransplant mortality ( P  = 0.0045) in comparison with those whose renal function recovered. The only predictor of HRS1 nonreversal was the duration of pretransplant dialysis with a 6% increased risk of nonreversal with each additional day of dialysis. In conclusion, our study suggests that patients with HRS1 should receive a timely liver transplant to improve their outcome. Liver Transpl 21:300–307, 2015 . © 2015 AASLD.